METHODS OF STUDYING ECOLOGICAL FUNCTIONS OF GEOGRAPHICAL NAMES (Scientific journal of the Fergana State University, 2023)
This article talks about the stages and methods of research used in toponymy, and also shows and analyzes the interdisciplinary essence and specific methods of researching ecological toponyms, a new direction in toponymy.